2019
DOI: 10.1021/acs.jpcc.9b05413
|View full text |Cite
|
Sign up to set email alerts
|

Selective Excited-State Dynamics in a Unique Set of Rationally Designed Ni Porphyrins

Abstract: In this work, we report the design and photophysical properties of a unique class of Ni porphyrins, in which the tert-butyl benzene substituents at the meso positions of the macrocycle were tethered by ethers with alkyl linkers. This not only results in the permanently locked ruf distortion of the macrocycle but also enables the engineering of the degree of distortion through varying the length of alkyl linkers, which addressed the complication of uncertainty in the specific structural distortions that has lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
(84 reference statements)
1
11
0
Order By: Relevance
“…Comparatively longer decay time is observed in case of Cu-TCBD ( 3 ) porphyrin. Similar, transient dynamics were observed in different Ni-porphyrins, which showed that the excited state lifetime could be varied in the range of 0.7–560 ps. …”
Section: Resultssupporting
confidence: 60%
“…Comparatively longer decay time is observed in case of Cu-TCBD ( 3 ) porphyrin. Similar, transient dynamics were observed in different Ni-porphyrins, which showed that the excited state lifetime could be varied in the range of 0.7–560 ps. …”
Section: Resultssupporting
confidence: 60%
“…In molecular systems, such timeresolved EXAFS investigations are possible. 44 Interestingly, there is a report of using electron paramagnetic resonance (EPR) with a guest molecule reporter to investigate temperature-induced structural changes in MOFs. 123 This opens the possibility of time-resolved EPR as a potential strategy in certain cases, such as with a guest molecule reporter in a MOF that does not give background signal in order to infer photoinduced structural changes.…”
Section: Overview and Time-resolved Techniques Appliedmentioning
confidence: 99%
“…Despite this, one clear signature that can be relied upon is an edge shift corresponding to a change in binding energy or oxidation state of the probed atom. Further information can be gathered above the transition edge where interference patterns between the probed atom and its neighbors can be analyzed using Fourier-transform techniques to provide excited state local structure information . In practice, the X-ray absorption spectrum is collected at discrete energies with and without laser excitation, and a difference spectrum is generated by subtracting laser on–laser off spectra …”
Section: Overview Of Time-resolved Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, AXMP can efficiently capture sub-ns XTA sample dynamics, which are often of particular interest. [14][15][16][17][18][19][20][21][22][23] This is accomplished using a carefully selected pump laser repetition rate, which makes the acquired time delays increase by δt in each subsequent pump-probe cycle. For example, in Fig.…”
Section: Introductionmentioning
confidence: 99%